A Reading of the Laws on the Protection of Antiquities in Libya (1914-1994) "The Right of Ownership, Usufruct, Expropriation, Compensation, and Excavation Licensing as a Model": A Reading of the Laws on the Protection of Antiquities in Libya (1914-1994) (Journal of Humanitarian and Applied Sciences, 2025)
Libyan legislation has consistently sought to define tangible and intangible antiquities of historical and archaeological value, whether already uncovered or expected to be found through excavation. Over time, it has refined these definitions through successive laws aimed at safeguarding the nation’s cultural heritage and ensuring that legal texts remain precise, coherent, and responsive to ongoing developments. These laws address key aspects of antiquities protection, covering ownership rights, use, and the procedures for expropriation and compensation. They also regulate the issuance of excavation permits to ensure responsible archaeological work. Research shows that the state has continually amended and updated its legal framework to close gaps and strengthen heritage protection. Despite these efforts, existing legislation still requires regular review to maintain its effectiveness as challenges and preservation needs evolve. Ongoing institutional coordination and public awareness are also essential to support the legal measures and ensure protection of Libya’s antiquities for future generations.
Keywords: Antiquities protection laws; ownership; – usufruct; expropriation; compensation